Statistical convergence of order ? for generalized difference sequences of fuzzy numbers - Altinok, Hifsi (Ios Press, 2014)
In this study we introduce the concepts of Lambda(m)-statistical convergence of order beta and strong Lambda(m)(p) - Cesaro summability of order beta for sequences of fuzzy numbers by helping many examples. Also, we establish some properties which are valid for sequences of real numbers, but not for sequences of fuzzy numbers.
Keywords: Fuzzy number; statistical convergence; cesaro summability; difference operator